An Optimized Protocol for the Synthesis of Peptides Containing trans‐Cyclooctene and Bicyclononyne Dienophiles as Useful Multifunctional Bioorthogonal Probes. Issue 54 (3rd August 2021) - La–Venia, Agustina; Dzijak, Rastislav; Rampmaier, Robert; Vrabel, Milan
Abstract: Despite the great advances in solid‐phase peptide synthesis (SPPS), the incorporation of certain functional groups into peptide sequences is restricted by the compatibility of the building blocks with conditions used during SPPS. In particular, the introduction of highly reactive groups used in modern bioorthogonal reactions into peptides remains elusive. Here, we present an optimized synthetic protocol enabling installation of two strained dienophiles, trans ‐cyclooctene (TCO) and bicyclononyne (BCN), into different peptide sequences. The two groups enable fast and modular post‐synthetic functionalization of peptides, as we demonstrate in preparation of peptide‐peptide and peptide‐drug conjugates. Due to the excellent biocompatibility, the click‐functionalization of the peptides can be performed directly in live cells. We further show that the introduction of both clickable groups into peptides enables construction of smart, multifunctional probes that can streamline complex chemical biology experiments such as visualization and pull‐down of metabolically labeled glycoconjugates. The presented strategy will find utility in construction of peptides for diverse applications, where high reactivity, efficiency and biocompatibility of the modification step is critical. Abstract : A simple methodology for the introduction of two strained dienophiles, bicyclononyne (BCN) and trans ‐cyclooctene (TCO), into synthetic peptides is presented. The method is based on the post‐synthetic attachment of the clickable groups to lysine residues after selective deprotection steps. The resulting peptides can be used for construction of useful peptide conjugates in highly efficient and biocompatible manner via two orthogonal click reactions, the strain‐promoted azide‐alkyne cycloaddition (SPAAC) and the inverse electron‐demand Diels‐Alder reaction (iEDDA).